2016
DOI: 10.1038/srep26865
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ketamine exposure causes abnormal development of prefrontal cortex in rat

Abstract: Ketamine is commonly used for anesthesia and as a recreational drug. In pregnant users, a potential neurotoxicity in offspring has been noted. Our previous work demonstrated that ketamine exposure of pregnant rats induces affective disorders and cognitive impairments in offspring. As the prefrontal cortex (PFC) is critically involved in emotional and cognitive processes, here we studied whether maternal ketamine exposure influences the development of the PFC in offspring. Pregnant rats on gestational day 14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 47 publications
(65 reference statements)
3
43
0
9
Order By: Relevance
“…Ketamine seems to also impair adequate neurodevelopment, as it induces neural loss in hippocampal CA3 region, pyramidal neurons abnormalities and reduced cell proliferation in the hippocampus (Zhao et al, ). Other side effects of ketamine include depression and anxiety‐like behaviors, impaired spatial memory, up‐regulation of the NR2A receptor subunit, down‐regulation of the NR2B subunit, the brain‐derived neurotrophic factor (BNDF) and post synaptic density protein 95 (PSD‐95) (Zhao et al, ), and neural loss in the medial prefrontal cortex (Zhao et al, ). Although the use of ketamine is not recommended during pregnancy, it continues to be used as either a recreational drug, or it is administered in cases where no other alternative is available (Craven, ; Knisely et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine seems to also impair adequate neurodevelopment, as it induces neural loss in hippocampal CA3 region, pyramidal neurons abnormalities and reduced cell proliferation in the hippocampus (Zhao et al, ). Other side effects of ketamine include depression and anxiety‐like behaviors, impaired spatial memory, up‐regulation of the NR2A receptor subunit, down‐regulation of the NR2B subunit, the brain‐derived neurotrophic factor (BNDF) and post synaptic density protein 95 (PSD‐95) (Zhao et al, ), and neural loss in the medial prefrontal cortex (Zhao et al, ). Although the use of ketamine is not recommended during pregnancy, it continues to be used as either a recreational drug, or it is administered in cases where no other alternative is available (Craven, ; Knisely et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, several studies have shown an association between both anesthetic exposure and drug abuse during pregnancy with future cognitive and neurobiological impairments of the offspring (Ing et al, ; Su, Chang, & Chen, ). Moreover, the effects of general anesthesia and ketamine in the neurodevelopment of the fetus and their consequences after birth are intensively evaluated (Abekawa et al, ; Brambrink et al, ; Ing et al, ; Kong et al, ; Slikker et al, ; Su et al, ; Zhao et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Early-life exposure to ketamine is toxic to the developing brain. One study found that maternal administration of ketamine during pregnancy caused widespread apoptosis in the fetal brain, neuronal loss, and disturbances in the maturation of pyramidal neurons in offspring [16]. In addition, maternal exposure to ketamine is associated with emotional disorders, such as anxiety and depression-like behavior, and cognitive impairment in offspring [17,18].…”
Section: Neurotoxic Effects Of Ketaminementioning
confidence: 99%
“…Ketamine anaesthesia interrupts the transfer of information between cortical areas in Rhesus monkeys and humans [43,44]. Prenatal anaesthesia, with ketamine or sevoflurane, causes neuronal loss and dysplasia of pyramidal neurons in the prefrontal cortex of rat pups [45,46]. Stimulation of the same cells alleviates ADHD signs [33].…”
Section: Prefrontal Cortexmentioning
confidence: 99%
“…Clinical studies [7][8][9][10][11][12][13][14][15] Animal studies [16][17][18][19][20] Neural molecular mechanisms Dopamine receptor [6,[21][22][23][24][25][26][27][28] N-methyl-D-aspartic acid receptor [29][30][31][32][33][34][35][36] Brain-derived neurotrophic factor [37][38][39][40][41] Neural network mechanisms Prefrontal cortex [33,[42][43][44][45][46][47][48][49][50] Synaptogenesis [7,33,[47][48][49]…”
Section: Content Referencesmentioning
confidence: 99%